2014
DOI: 10.1371/journal.pone.0111627
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Screening for MRSA: Different Swabs – Different Results!

Abstract: ObjectivesSwab-based nasal screening is commonly used to identify asymptomatic carriage of Staphylococcus aureus in patients. Bacterial detection depends on the uptake and release capacities of the swabs and on the swabbing technique itself. This study investigates the performance of different swab-types in nasal MRSA-screening by utilizing a unique artificial nose model to provide realistic and standardized screening conditions.MethodsAn anatomically correct artificial nose model was inoculated with a numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 68 publications
(83 reference statements)
3
31
0
9
Order By: Relevance
“…Swabs and, to lesser extent, tissue biopsies are used for microbiological analyses from sites of infection. For swab-based analyses, the microbiological yield is dramatically influenced by the sampling device itself (Warnke et al, 2014a(Warnke et al, , 2014b, as well as by the sampling technique (Warnke et al, 2014c). For tissue specimen analyses, the microbiological yield detectable in the laboratory is primarily determined by the processing of the sample, since detection only depends on the microbiological quantities present in the sample and not on the uptake and release capacities of the sampling device.…”
Section: Discussionmentioning
confidence: 99%
“…Swabs and, to lesser extent, tissue biopsies are used for microbiological analyses from sites of infection. For swab-based analyses, the microbiological yield is dramatically influenced by the sampling device itself (Warnke et al, 2014a(Warnke et al, , 2014b, as well as by the sampling technique (Warnke et al, 2014c). For tissue specimen analyses, the microbiological yield detectable in the laboratory is primarily determined by the processing of the sample, since detection only depends on the microbiological quantities present in the sample and not on the uptake and release capacities of the sampling device.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there are significant differences between different types of swabs in terms of true‐positive or false‐negative detection rates of nasal MRSA colonization . Under study conditions, the highest sensitivity was achieved using a flocked swab combined with Amies liquid medium . Such a swab may therefore be recommended in order to increase the sensitivity of pathogen detection.…”
Section: Resultsmentioning
confidence: 96%
“…The nose is the main reservoir for S. aureus, which can be distributed into the respiratory tract and to the surface of the skin and even to the surrounding air during exhalation [22]. However, colonization of S. aureus can be seen in several human body sites, the anterior nares are the most common carriage site for this organism [23].…”
Section: Discussionmentioning
confidence: 99%
“…Given that MRSA is a cross cutting problem affecting both health-care settings as well as the community, it is essential to include evidence from these settings too. Secondly, the small size of the study (22 …”
Section: Acknowledgmentsmentioning
confidence: 99%